Cat Scratch Disease Presenting as Breast Cancer: A Report of an Unusual Case. (13th March 2013) - Iannace, Carlo; Lo Conte, Domenico; Di Libero, Lorenzo; Varricchio, Antonio; Testa, Antonio; Vigorito, Raffaella; Gagliardi, Giuliano; Lepore, Maria; Caracciolo, Francesco
Abstract : Benign lymphoreticulosis (cat scratch disease, CSD) may have a clinical course that varies from the most common lymphadenitis localized in the site of inoculation, preceded by the typical "primary lesion, " to a context of severe systemic involvement. Among these uncommon clinical aspects, there is mammarian granulomatous lymphadenitis which may appear as a mastitis or a solitary intraparenchymal mass, giving the impression of a breast tumor. In these cases, intensive clinical, instrumental, and laboratory investigations are necessary to exclude malignancy. Because of its rarity, in equivocal cases, it is reasonable to use surgical excision for accurate histological examination. We report a case of CSD of the breast in a 59-year-old woman, analyzing the clinical, histopathological, and instrumental appearance and also performing a literature review.